Effect of Gamma Irradiation on Pathogenic Staphylococcus aureus in Packaged Ready-to-Eat Salads Treated with Biological Extracts - Zernadji, Widad; Jebri, Sihem; Rahmani, Faten; Amri, Ismail; Aissaoui, Dorra; Trabelsi, Med Hedi; Yahya, Mariem; Amri, Islem; Hmaied, Fatma (Journal of food protection, 2024)
•T. capitatus EO can be considered safe for human consumption at low concentrations.•Synergistic activities of biological extracts and low dose γ-irradiation were observed.•T. capitatus EO combined with γ-irradiation reduced S. aureus to undetectable levels.•Myrtle juice combined with γ-irradiation significantly inhibited S. aureus.•The combination treatments can provide safe RTE salads for immunocompromised patients. Providing pathogen-free ready-to-eat (RTE) salads is critical for all consumers, especially individuals with weakened immunity. In this study, the efficacy of γ-irradiation on Staphylococcus aureus (S. aureus) in freshly packaged salads (4.24 log CFU/g) treated with essential oil (EO) and myrtle juice during 10 days of storage and their impact on organoleptic properties were investigated. EO was extracted by hydrodistillation and the chemical composition was analyzed by gas chromatography with Flame Ionization Detector (GC/FID) and gas chromatography/mass spectrometry (GC/MS). Myrtle juice was prepared from fresh fruits. The cytotoxic effects of Thymus capitatus (T. capitatus) EO against a normal human umbilical vein endothelial cell (HUVEC) were assessed. GC/FID and GC–MS analysis of the thyme EO revealed the presence of 13 compounds, including carvacrol (79.55%) and p-cymene (7.93%) as major components. The EO was found to be noncytotoxic, with concentrations lower than 0.16 µL/mL. A reduction of more than 3 log CFU/g and a total inactivation of S. aureus were achieved with the combination of gamma irradiation at 0.5 kGy with myrtle juice at 6 µL/mL and EO at 0.08 µL/mL, respectively. The treatment of fresh RTE salads with thyme and myrtle juice was evaluated as acceptable by the sensory panel. The combined effect showed a synergistic potential on the inactivation of S. aureus.